1985
DOI: 10.3109/00365528509091652
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphy, Ph Measurement, and Radiography in the Evaluation of Gastroesophageal Reflux

Abstract: Scintigraphy as a diagnostic tool has been explored in 69 patients with gastroesophageal reflux (GER) symptoms and endoscopic esophagitis. In all subjects the presence of reflux was also evaluated by radiography and intraesophageal pH measurements (standard acid reflux test). The overall sensitivity of scintigraphy (85.5%) was significantly higher than those of radiography (27.5%) and pH measurements (69.5%). Scintigraphy was performed with normal saline and with acidified orange juice as the transport medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…In 1984, Cargill in France found that scintigraphy could be used to evaluate the reflux of food in the development of pulmonary disorders 11 . Later studies demonstrated that the use of acidified food increased the correlation between food and acid reflux, leading to the conclusion that gamma scintigraphy was detecting the reflux of neutral materials which could not be detected by pH monitoring 12 , . 13 By 1986, largely due to the work of Kaul and co‐workers, scintigraphic reflux could be detected in 92% and 79% of the patients with and without histologic evidence of oesophagitis 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1984, Cargill in France found that scintigraphy could be used to evaluate the reflux of food in the development of pulmonary disorders 11 . Later studies demonstrated that the use of acidified food increased the correlation between food and acid reflux, leading to the conclusion that gamma scintigraphy was detecting the reflux of neutral materials which could not be detected by pH monitoring 12 , . 13 By 1986, largely due to the work of Kaul and co‐workers, scintigraphic reflux could be detected in 92% and 79% of the patients with and without histologic evidence of oesophagitis 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in this series of events can result in various clinical symptoms and pathologic changes in the esophagus. Important esophageal motor function changes have been reported based on the pH monitoring and manometric, radiological, and scintigraphic studies in such patients [10][11][12][13]. For example, decreased peristaltic activity, increased nonpropulsive waves, irregular esophageal contractions, and diminished esophageal peristalsis were observed during GER episodes in previous studies [14,15].…”
Section: Discussionmentioning
confidence: 88%
“…Hasta un 50 % de la población sana puede presentar hernia de hiato [83], por lo que su diagnóstico no implica padecer ERGE. Por otra parte, la mitad de los enfermos con ERGE sintomática no tienen hernia de hiato [84]. De esta forma, se asume que es una condición facilitadora pero no imprescindible ni necesaria en la ERGE [85].…”
Section: Hernia De Hiatounclassified